What is the status of immunotherapy in thyroid neoplasms? - Garcia-Alvarez, Alejandro; Hernando, Jorge; Carmona-Alonso, Ana; Capdevila, Jaume (Frontiers in Endocrinology, 2022)
Immunotherapy has changed the treatment of patients with advanced cancer, with different phase III trials showing durable responses across different histologies. This review focuses on the preclinical and clinical evidence of potential predictive biomarkers of response and efficacy of immunotherapy in thyroid neoplasms. Programmed death-ligand 1 (PD-L1) staining by immunohistochemistry has shown higher expression in anaplastic thyroid cancer (ATC) compared to other subtypes. The tumor mutational burden in thyroid neoplasms is low but seems to be higher in ATC. Immune infiltrates in the tumor microenvironment (TME) differ between the different thyroid neoplasm subtypes. In general, differentiated thyroid cancer (DTC) has a higher number of tumor-associated lymphocytes and regulatory T cells (Tregs), while ATC and medullary thyroid cancer (MTC) display a high density of tumor-associated macrophages (TAMs). Nevertheless, results from clinical trials with immunotherapy as monotherapy or combinations have shown limited efficacy. Further investigation into new strategies aside from anti-cytotoxic T-lymphocyte antigen 4 (CTLA-4)/programmed death 1 (PD-1)/PD-L1 antibodies, validation of predictive biomarkers, and better population selection for clinical trials in thyroid neoplasms is more than needed in the near future.